Les pôles d’excellence comme facteur de compétitivité et d’attractivité des territoires : l’exemple de la métropole lilloise - Ludivine Malaterre-Vaille (EchoGéo)
Since the late 1970s, the Lille region has had to face an unprecedented crisis which called its development model into question. The model was based on very large industries, such as the textile or mining industry. A drastic change was needed, and the Lille region, like other French regions, recognized the major role played by research and innovation in territorial development. As a consequence, research and innovation clusters have sprung up at the regional level since the late 1990s, fostered by local, regional and national public policies. This recent phenomenon raises many questions, especially regarding the articulation of these policies within the regional territory and the impact of such clustering patterns. To try to answer these questions, this study will focus more specifically on excellence clusters in the Lille metropolitan area, based on a survey of companies from one of these clusters. This survey shows us that the requirement of land profitability was sometimes made to the detriment of the ambitions posted at first.